IMPLEMENTATION OF A WEB-BASED EXPERT SYSTEM FOR DIAGNOSIS OF RED BLOOD CELL PRODUCTION DISORDERS - Raden Bagus Bambang Sumantri; Imam Ahmad Ashari; Hadi Jayusman (LPPM STMIK Pringsewu, 2022)
The expert system is one of the branches of artificial ingenuity that studies how to adopt an expert's way of thinking in solving a problem and making a decision to draw conclusions. In this case an expert system is used to diagnose anemic diseases. Problems that arise in the community such as not knowing the characteristics of the disease, its impact is felt for a long time, and being lazy to consult a doctor. Overcoming these problems takes a lot of time and money, so an application is needed that can help doctors diagnose web-based red blood cell production disorders. The use of web technology combined with expert systems in supporting decisions, can better socialize the system. The data collection methods used are literature study methods, interviews with health experts and documentation. Fact-finding in expert systems uses the forward chaining method, to seek conclusions from existing facts. The application development phase includes interface design and system testing. The result of this study is to produce an output in the form of an application to diagnose impaired red blood cell production. The black box test shows that the program is in accordance with the knowledge of health experts regarding impaired red blood cell production.